An empirical case study on Stack Overflow to explore developers’ security challenges - Rahman, Muhammad Sajidur (Kansas State University, 2016)
The unprecedented growth of ubiquitous computing infrastructure has brought new challenges for security, privacy, and trust. New problems range from mobile apps with incomprehensible permission (trust) model to OpenSSL Heartbleed vulnerability, which disrupted the security of a large fraction of the world's web servers. As almost all of the software bugs and flaws boil down to programming errors/misalignment in requirements, we need to retrace back Software Development Life Cycle (SDLC) and supply chain to check and place security & privacy consideration and implementation plan properly. Historically, there has been a divergent point of view between security teams and developers regarding security. Security is often thought of as a "consideration" or "toll gate" within the project plan rather than being built in from the early stage of project planning, development and production cycles. We argue that security can be effectively made into everyone's business in SDLC through a broader exploration of the users and their social-cultural contexts, gaining insight into their mental models of security and privacy and usage patterns of technology, trying to see why and how security practices being satisfied or not-satisfied, then transferring those observations into new tool building and protocol/interaction design. The overall goal in our current study is to understand the common challenges and/or misconceptions regarding security-related issues among developers. In order to investigate into this issue, we conduct a mixed-method analysis on the data obtained from Stack Overflow(SO), one of the most popular on-line QA sites for software developer community to communicate, collaborate, and share information with one another. In this study, we have adopted techniques from mining software repositories research paradigm and have employed topic modeling for analyzing security-related topics in SO dataset. To our knowledge, our work in SO data mining is one of the earliest systematic attempts to understand the roots of challenges, misconceptions, and deterrent factors, if any, among developers while they try to implement security features during software development. We argue that a proper understanding of these issues is a necessary first step towards "build security in" culture in SDLC.
Keywords: Mining; Software Security; Security & Privacy; Software Engineering; Topic Model; Stack Overflow